Kinase Sensing Based on Protein Interactions at the Catalytic Site. Issue 17 (11th March 2022) - Solomon, Ohad; Sapir, Hannah; Mervinetsky, Evgeniy; Chen, Yu‐Ju; Friedler, Assaf; Yitzchaik, Shlomo
Abstract: Invited for the cover of this issue is Assaf Friedler, Shlomo Yitzchaik and co‐workers at the Hebrew University of Jerusalem and the Academia Sinica. The image depicts a new approach for electrochemical kinase sensing that does not rely on phosphorylation. The kinase binds a peptide layer, which undergoes rearrangement, resulting in the permeation of redox‐active species through the layer and electrochemical sensing. Read the full text of the article at 10.1002/chem.202104227 . Abstract : " … we developed a new approach for electrochemical kinase biosensing that does not rely on enzymatic phosphorylation detection… " This and more about the story behind the front cover can be found in the article at 10.1002/chem.202104227 ).